2008
DOI: 10.2341/07-27
|View full text |Cite
|
Sign up to set email alerts
|

Fracture Resistance and Gap Formation of MOD Restorations: Influence of Restorative Technique, Bevel Preparation and Water Storage

Abstract: ©Operative Dentistry, 2008, 33-1, 37-43 SUMMARYThis in vitro study evaluated the effect of technique, use of a bevel and thermal cycling on the fracture resistance and gap formation of resin composite MOD restorations. Fracture resistance was measured on standard MOD cavities prepared in 100 upper premolars that were stored for 24 hours and 6 months with 1000 thermal cycles. Subgroups (n=10) were: beveled or nonbeveled preparations and direct restorations (Adper Single Bond/Filtek Z250) and indirect restor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
51
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 19 publications
3
51
0
1
Order By: Relevance
“…Advances in polymers and fillers have significantly enhanced the composite properties and clinical performance [511]. However, a serious drawback is that composites tend to accumulate more biofilms/plaques in vivo than tooth enamel and other restorative materials [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Advances in polymers and fillers have significantly enhanced the composite properties and clinical performance [511]. However, a serious drawback is that composites tend to accumulate more biofilms/plaques in vivo than tooth enamel and other restorative materials [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…While some studies reported higher fracture resistance for direct [9] and indirect resin composite restorations [10], other studies revealed no significant differences [11,12].…”
Section: Discussionmentioning
confidence: 94%
“…A técnica visa basicamente aumentar a área de exposição dos prismas de esmalte com o intuito de aumentar a retenção da restauração e mascarar a interface entre o esmalte e o composto a fim de melhorar a estética. A única desvantagem descrita desse procedimento é que há a necessidade de desgaste de uma pequena quantidade de estrutura dental 33 . Cavidades preparadas com bisel em esmalte apresentam comportamento semelhante ao das que não foram biseladas, mas proporcionam melhor vedamento marginal, diminuindo a microinfiltração 34 .…”
Section: Discussionunclassified